The safety of current treatment options for advanced esophageal cancer after first-line chemotherapy. Issue 1 (2nd January 2022) - Ikeda, Go; Yamamoto, Shun; Kato, Ken
ABSTRACT: The prognosis of advanced esophageal cancer (EC) remains poor, and few effective agents are available. For advanced EC patients, a combination of platinum and fluoropyrimidine is recognized as the standard first-line treatment. After first-line treatment, taxane or irinotecan has been used. Based on the KEYNOTE-181 and the ATTRACTION-3 trials, immune checkpoint inhibitors (ICIs) such as pembrolizumab and nivolumab appear to prolong survival, compared with cytotoxic agents, as second-line treatments for advanced EC patients. In addition, ICIs have different safety profiles than conventional cytotoxic agents. Herein, we discuss the differences in the safety profiles of cytotoxic agents and ICIs for the treatment of advanced EC patients after first-line chemotherapy.ICIs as a second-line treatment are tolerable in advanced EC patients. Although infrequent, ICIs can cause immune-related adverse events that are sometimes fatal. Therefore, regular monitoring of physical and laboratory examinations is needed during and after the administration of ICIs. As the major toxicities of taxane are neutropenia and neuropathy, while those of irinotecan are neutropenia and diarrhea, appropriate supportive care or dose modification may be needed for individual patients. ICI-containing treatments have been developed not only as second-line treatments, but also as first-line treatments or for use in perioperative settings; thus, particular attention with regard to immune-related toxicities is needed.